The Intervening Effect of Business Strategy to the Relationship between Internal and External Business Environmental and Performance among Micro and Small Industry Cluster Services and Creative Industry in Jakarta, Indonesia - Wibowo, Prasetio Ari (2022)
This research aims to determine external business environmental factors which influence the measurement of business performance levels, to identify internal environmental factors/ RBV includes resources, efficiency, capabilities and competitive advantages that influence the measurement of business performance levels in MSMEs and creative industry service clusters in DKI Jakarta. To identify external & environmental business environmental factors internal/RBV which influences the measurement of business performance levels in the MSME service cluster and creative industry in DKI Jakarta. To identify and confirm the impact of Resource-Based Policies Perspective strategy indicators (RBV) and I/O indicators in making business strategies for micro, small and medium enterprises (MSMEs) operating in the service and creative industry cluster in DKI Jakarta. To identify the influence of business strategy on business performance in MSMEs in the service and creative industry cluster in DKI Jakarta. This research uses semi structured interviews and questionnaires. Data was collected using a purposive sampling method from 365 business actors operating in the creative and service economy sectors in DKI Jakarta. Data analysis uses the PLS-SEM method. The findings of this study indicate that The internal environment (RBV theory) influences the performance of businesses operating in the MSME service and creative sector clusters in DKI Jakarta, The external environment (I/O theory) affects the business performance of communities of MSME service and creative industries in DKI Jakarta, Business strategy influences the performance of micro, small and medium enterprises (MSMEs) in the service and creative industry clusters in DKI Jakarta, The RBV and I/O theories affect on the business performance of small and medium-sized enterprises (SMEs) in the service and creative sector cluster in DKI Jakarta, The Resource-Based View (RBV) and I/O theories affect the business strategies of service cluster SMEs and creative industries in DKI Jakarta. Hence, enhancing the business strategy and performance of small and medium enterprises (SMEs) operating in the service sector and creative economy within DKI Jakarta, specifically by augmenting the internal and external business environments that consistently yield positive outcomes, can lead to an enhancement in company performance.